The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1108/bjm-02-2022-0051
|View full text |Cite
|
Sign up to set email alerts
|

Motivational background of work addiction: the role of perceived demanding organizational conditions

Abstract: PurposeIn the literature, work addiction is proposed to be considered a construct that requires an extensive approach for understanding it; consequently, it should be analyzed as the interaction between personal and situational factors. Therefore, the aim of the present study was to examine the mediating role work motivation plays in the relationship between perceived demanding organizational conditions and employee work addiction.Design/methodology/approachA cross-sectional study was conducted on a convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(128 reference statements)
1
4
0
Order By: Relevance
“…The industry is so peculiar that none of the employees has an alternative work environment than resort to brain drain behaviour in other international countries where their competence and ability will be fully appreciated and rewarded with minimal stress and work pressure. This outcome is consistent with the study of Gubik and Vörös (2023) and Morkevičiūtė and Endriulaitienė (2023) whose discoveries had it that quest to be financially buoyant and attitude of growing career for employees in Europe has transformed them to workaholics and it is adversely influencing their QWL.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…The industry is so peculiar that none of the employees has an alternative work environment than resort to brain drain behaviour in other international countries where their competence and ability will be fully appreciated and rewarded with minimal stress and work pressure. This outcome is consistent with the study of Gubik and Vörös (2023) and Morkevičiūtė and Endriulaitienė (2023) whose discoveries had it that quest to be financially buoyant and attitude of growing career for employees in Europe has transformed them to workaholics and it is adversely influencing their QWL.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…There are numerous potential explanations of the links between significant others and an individual in terms of work addiction. These include, for instance, external benefits provided by addicted authoritative others for hard work of an individual (Morkevičiūtė & Endriulaitienė, 2022b, 2023a), a narrow understanding of a person's worth when addicted significant others evaluate an individual on account of his/her performance and achievements (Robinson, 2014), over‐responsibility assigned to an individual by addicted significant others (Robinson, 1998, 2014) or even sleep patterns, since poor sleep quality of addicted significant people may control their stress levels, and, ultimately, shape the behavior of those around them (Atroszko & Atroszko, 2020). The following paragraphs introduce the explanatory mechanisms that were most widely discussed in the scientific literature on this field.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Thus, it is not surprising that scholars have documented that intrinsic and identified motivation are negatively correlated with job burnout and that introjected and external regulation, as well as amotivation, are positively associated with burnout (Fernet et al, 2008). Previous studies have shown that workload among workers from different organizations in Lithuania was positively related to extrinsic work motivation and did not relate to intrinsic work motivation (Morkevičiūtė & Endriulaitienė, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This results in six types of motivation aligned along the self-determination continuum. First, intrinsic motivation refers to performing an activity because it is inherently enjoyable, challenging, and interesting (Morkevičiūtė & Endriulaitienė, 2023). Intrinsically motivated teachers work voluntarily without expecting any rewards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation